Effectiveness of Integrated Language Skills-Based Student Worksheets for Elementary School Students - Tiarnita Maria Sarjani Br. Siregar; Christine Helena Natalia; Nanda Ramadani; Hesti Fibriasari; Savitri Rahmadany (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Language learning during the formative years of elementary education serves as the foundation for students’ academic, social, and cognitive growth. Mastery of language enables students not only to communicate effectively but also to think critically, collaborate with peers, and comprehend a wide range of academic content. This study investigates the effectiveness of integrated language skills-based student worksheets in improving the English proficiency of elementary school students. Conducted in two public schools in Medan, Indonesia, the quasi-experimental research involved 60 fourth-grade students divided into experimental and control groups. The experimental group utilized worksheets designed to integrate listening, speaking, reading, and writing skills based on thematic content, while the control group used conventional skill-separated materials. Data were collected through pre-tests, post-tests, observations, and student self-assessments. Findings revealed that students in the experimental group showed significantly greater improvements in all four language skills. They also demonstrated higher levels of engagement, confidence, and motivation. The study concludes that integrated worksheets provide a more holistic and effective approach to language learning, supporting communicative competence and student-centered learning. These results underscore the importance of designing instructional materials that reflect authentic language use and curricular goals. Integrated language skills-based student worksheets have been proven effective in improving the language competence of elementary school students.